Hubungan Cakupan Pelayanan Kesehatan Ibu Hamil, Ibu Bersalin, dan Ibu Nifas dengan Angka Kematian Ibu di Provinsi Jawa Timur - Rahmah Christiawan; Lutfi Agus Salim; Sarah Christiawan (Jurnal Kesehatan Komunitas, 2023)
Maternal mortality in Indonesia is known to be a concern to be able to achieve targets in accordance with the focus on SDGs and achieve adequate maternal health services in terms of access and quality. One of the urgencies for strategies to reduce maternal mortality is to map the factors associated with maternal mortality and identify the implementation that is carried out. This study aims to analyze the relationship between coverage of health services for pregnant women, delivery mothers, and postpartum women with maternal mortality in East Java, quantitative type research with a correlational approach conducted with secondary data, in the East Java Health Profile from 2019 to 2021. Variables in this study include maternal mortality coverage of health services for pregnant women, delivery mothers, and postpartum women (ANC for pregnant women K1, ANC for pregnant women K4, delivery assisted by health workers, delivery conducted at health services, KF 1, KF 2 and KF 3 postpartum women. The results of the study found that the variables correlated with maternal mortality in East Java from 2019 to 2021 coverage of health services for mothers during pregnancy, delivery mothers, and postpartum.